Membangun Perdamaian di Indonesia melalui Tradisi Makan Nasi Tumpeng: Dialog Antaragama di Tingkat Akar Rumput - Gunawan, Linna (STFT Jakarta, Indonesia, 2023)
Is there a way to build peace without violence in Indonesia? The question arises as a reflection of the complexity of conflict in Indonesia. In answering this question, this article provides a description of the causes of conflict from conflict theory and seeks its equivalence with several conflict events in Indonesia. Furthermore, David P. Barash’s peacebuilding theory appears in this article as an alternative to building peace; specifically, Marianne Farina’s nonviolence peace theory becomes the author’s choice for peacebuilding in Indonesia. With the aim of providing a concrete example of a nonviolent peacebuilding approach, this article describes an interfaith dialogue using a local Indonesian tradition, namely eating Nasi Tumpeng, as a first step of the approach. This tradition provides a space for the creation of interfaith dialogue at the grassroots level to discuss conflicts using the values contained in this eating tradition, namely strong relational values between humans and God, fellow humans, and even the environment.